Multiple congenital anomalies-hypotonia-seizures syndrome is caused by a mutation in PIGN. Issue 6 (14th April 2011) - Maydan, Gal; Noyman, Iris; Har-Zahav, Adi; Neriah, Ziva Ben; Pasmanik-Chor, Metsada; Yeheskel, Adva; Albin-Kaplanski, Adi; Maya, Idit; Magal, Nurit; Birk, Efrat; Simon, Amos J; Halevy, Ayelet; et al.
Abstract : Background: This study reports on a hitherto undescribed autosomal recessive syndrome characterised by dysmorphic features and multiple congenital anomalies together with severe neurological impairment, chorea and seizures leading to early death, and the identification of a gene involved in the pathogenesis of the disease. Methods: Homozygosity mapping was performed using Affymetrix Human Mapping 250k NspI arrays. Sequencing of all coding exons of the candidate genes was performed with primer sets designed using the Primer3 program. Fluorescence activated cell sorting was performed using conjugated antibody to CD59. Staining, acquisition and analysis were performed on a FACSCalibur flow cytometer. Results: Using homozygosity mapping, the study mapped the disease locus to 18q21.32–18q22.1 and identified the disease-causing mutation, c.2126G→A (p.Arg709Gln), in PIGN, which encodes glycosylphosphatidylinositol (GPI) ethanolamine phosphate transferase 1, a protein involved in GPI-anchor biosynthesis. Arginine at the position 709 is a highly evolutionarily conserved residue located in the PigN domain. The expression of GPI linked protein CD59 on fibroblasts from patients as compared to that in a control individual showed a 10-fold reduction in expression, confirming the pathogenic consequences of the mutation on GPI dependent protein expression. Conclusions: The abundant expression of PIGN in various tissues is compatible with the diverse phenotypic features observed in the patients and with the involvement of multiple body systems. The presence of developmental delay, hypotonia, and epilepsy combined with multiple congenital anomalies, especially anorectal anomalies, should lead a clinician to suspect a GPI deficiency related disorder.